The Analysis Study of Effects of Oral Antidiabetic Drugs on Tuberculosis Risk and Treatment Outcomes : A Comprehensive Systematic Review - Setiafadi, Rachmad Alsy; Nida, Nor Anisatun; Marom, Muhammad Naufal (International Medical Journal Corp. Ltd, 2024)
Background: Diabetes mellitus triples the risk of infection, leading to poor clinical outcomes. Hyperglycemia suppresses immune responses, affecting TB and diabetes patients. Modulation of host cell responses and targeting pathogens could improve treatment outcomes and reduce drug resistance. Methods: Following PRISMA 2020 guidelines, this systematic review focused exclusively on full-text articles published in English between 2014 and 2024. Result: The study conducted a comprehensive review of over 600 publications sourced from reputable databases, including ScienceDirect, SagePub, and PubMed. Following an initial screening, eight publications were identified as warranting more in-depth analysis. Consequently, a thorough review of these selected studies was performed to ensure a detailed and rigorous evaluation. Conclusion: Metformin, an oral antidiabetic (OAD) agent, is associated with reduced incidence and mortality from active tuberculosis in patients with diabetes. In contrast, saxagliptin, another oral antidiabetic drug, is linked to an increased risk of active tuberculosis. The continuing examination of the association between metformin and tuberculosis risk highlights the need for further research to better elucidate and validate these associations.